Circumpolar health : proceedings of the 3rd International Symposium, Yellowknife, N.W.T. - Shephard, Roy J.; Itō, Shinji, 1912-2003 (University of Toronto Press, 2018)
his volume presents in tightly edited form more than ninety papers from the third international symposium on circumpolar health, held in Yellowknife in July 1974.